Submerged modular breakwaters for coastal protection - Teh, H.M. (WITPress, 2014)
Submerged breakwaters are widely used for establishment and protection of coastal wetlands; nevertheless, construction of breakwaters in the sea domain has always been a challenge to engineers. This research introduces a number of submerged breakwaters that are made of a plurality of rectangular/triangular concrete modules. The wave transmission characteristics of the breakwaters are evaluated using small-scale physical modelling. A series of experiments are conducted in a wave flume to study the performance of the breakwaters in regular waves. Wave suppression ability of the breakwaters is quantified by the wave transmission coefficient. The effects of breakwater width, face type and configuration on wave transmission of the breakwaters are addressed in this paper. Â© 2014 WIT Press.